Averaging of differential inclusions with many-valued pulses - Plotnikov, V. A.; Plotnikova, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We justify a method of complete and partial averaging on finite and infinite intervals for differential inclusions with many-valued pulses.